Integration of Fintech and CSR in Improving Financial Stability of Islamic Banks - Laila, Nazil Rizki; Rahmadhani, Sari (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2025)
This study examines the relationship between financial technology (Fintech), corporate social responsibility (CSR), and bank financial stability (BFS) in Islamic banks in Indonesia, with a particular focus on the role of fintech as a mediator. Using a quantitative approach, this study utilises secondary data from the annual and sustainability reports of Islamic banks listed on the Indonesia Stock Exchange (IDX) for 2021-2023. Data were analysed using the Partial Least Squares-Structural Equation Modelling (PLS-SEM) method. The results of the study show, first, that CSR has a significant direct effect on BFS and an indirect effect through fintech. Second, although the relationship between CSR and fintech is negative, fintech plays a crucial role in enhancing the financial stability of Islamic banks. Third, it was revealed that BFS does not significantly influence fintech, and although BFS does influence CSR, the mediating role in this relationship has not been proven. These findings emphasise the importance of an integrative and prudent approach in the adoption of fintech by Islamic banks. Although fintech can enhance stability, banks must continue to uphold their CSR commitments to prevent a decline in social initiatives, which could damage their long-term legitimacy and reputation. This research offers new insights into the complex interplay between social responsibility and technological innovation in Indonesia's distinct context of Islamic banking.